Muhammadiyah's Role in Overcoming the Covid-19 Pandemic through Preventive, Persuasive, And Spiritual Approaches In Southeast Sulawesi - Suhendi Syam; Dina Komalasari; Muslim Muslim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper aims to clearly describe the role of Muhammadiyah in dealing with the Covid-19 pandemic through a preventive, persuasive, and spiritual approach in Southeast Sulawesi so that people can experience firsthand some of the assistance provided by Muhammadiyah, especially for the people of the island of Buton. The research method used in this study is a qualitative-descriptive method. While the data collection uses three events, namely: 1). Documentation; 2). Focus Group Discussion (FGD); 3). In-depth interview or dialogue (In-dept Interview). Data processing is carried out inductively so that data collection and data processing are carried out simultaneously. The results of this study indicate that the Muhammadiyah Association in Southeast Sulawesi plays an active and real role in dealing with the covid 19 pandemic. The first action is through preventive measures which are also carried out based on the advice of the Prophet's hadith in tackling the dangers of disease so that it does not spread quickly. There are at least four preventive measures so that COVID-19 does not spread further in the community. 1). Stay at home (stay at home); 2). Social distancing (social restrictions); 3). Increase alms; 4). Maintain body immunity. Second, by approaching it through appropriate persuasive communication so that it can influence people to change their behavior in a positive direction. This persuasive effort includes various aspects, such as attitudes, behavior and knowledge of the target audience. The third effort with a Spiritual approach includes 1). Calling to increase patience is conveyed in every lecture and Friday sermon; 2). Prayer; 3). Zakat; and 4). Sacrifice Worship. This research is the output of the Muhammadiyah Research Grant Batch IV managed by the PP Muhammadiyah Diktilitbang Council for the 2020 funding year.